Effects of parasocial relationship, reality TV, and social media on celebrity endorsement. - CHUNG, Siyoung (Institutional Knowledge at Singapore Management University, 2014)
We examine the impact of operating synergies in horizontal mergers on the stock and operating performance of merging firms’ product market rivals, corporate customers, and suppliers. Using a unique dataset of merger-related synergy forecasts disclosed by firms’ insiders, we provide first direct evidence that horizontal merger synergies affect valuation and performance of rivals, customers, and suppliers in ways consistent with strategic effects predicted by industrial organization theory. More broadly, our results underscore the importance of inter-firm linkages for firms’ valuation and performance.